Growing food, growing food systems: The role of non-profit farms - DuPuis, E. Melanie; Christian, Annie (Frontiers in Sustainable Food Systems, 2023)
The study of nonprofit food organizations has focused primarily on food policy, urban gardens, coops, and farmers’ markets in cities. Despite significant research on these kinds of food non-profits, research specifically on non-profit farms – organizations that produce food for local communities – is nearly non-existent. We argue that non-profit farms are a category that deserves more research attention. This article asks what services nonprofit farms see themselves as providing to their communities, along with a supply of local food. We focus on the missions of nonprofit farms, using farms on the GuideStar database of nonprofit organizations. We also examine, through interviews and website analysis, the role of nonprofit farms in the Hudson Valley, long a hub of nonprofit farms. We conclude that local nonprofit farms are hybrid organizations that perform services that are similar to local community nonprofits, supporting local social welfare, environment, education, and community development roles, along with providing local food access and, in some cases, supporting food system change.